The Application of Affidavits in Bankruptcy Proceedings: A Comparative Study of Indonesia, Malaysia, and Singapore - Leonardus, Rado Fridsel; Shandy, Ricky; Adistia, Sheva Trisanda; Winanto, ‎; Wijayanta, Tata (KnE Social Sciences, 2025)
In bankruptcy cases, affidavits are commonly used as written evidence that is both effective and efficient for simple evidentiary procedures before the court. In countries adhering to the civil law system, such as Indonesia, affidavits are implicitly regulated under Article 1866 of the Civil Code (KUH Perdata) and Article 164 of the HIR/Article 284 of the RBg, classified as written evidence in the form of documents. On the contrary, in countries with common law systems, such as Malaysia and Singapore, the application of affidavits as evidence in bankruptcy cases differs significantly. This study aims to examine the application of affidavits in bankruptcy cases across several countries, including Indonesia, Malaysia, and Singapore. It employs normative legal research methods by analyzing legal documents within the context of bankruptcy law. The study utilizes statutory, conceptual, and comparative approaches, relying on secondary data collected through library research encompassing primary, secondary, and tertiary legal materials. The findings of this study indicate that in Indonesia, affidavits cannot be classified as authentic deeds and do not possess the characteristics of conclusive evidence, thus they cannot be equated with witness testimonies. However, affidavits can be used as ordinary written evidence to support other evidence, assisting judges in efficiently resolving bankruptcy cases within a limited examination period. In contrast, in Malaysia and Singapore, affidavits in bankruptcy cases are generally used as authentic deeds, sworn before a commissioner for oaths or notary public, and are required to be submitted as evidence by both creditors and debtors in court proceedings. Thus, the distinction between common law and civil law systems in the application of affidavits is clearly lied at their level as a tool of evidence in bankruptcy proceedings.